SURVEY SOSIAL EKONOMI DAN PELAYANAN AIR MINUM NON PELANGGAN PDAM DI KECAMATAN KALIWIRO KABUPATEN WONOSOBO - Ary Yunanto (Faculty of Economics and Business Universitas Jenderal Soedirman, 2010)
Economic activities and social survey of drinking water services to customers-households in the District of Wonosobo regency Kaliwiro aims to provide information on household characteristics, water resources and usage, the desire to become a customer PDAM and level of ability to pay, as well as socioeconomic households, especially who have not become a customer of PDAM Kabupaten Wonosobo. Based on the results of the analysis Kaliwiro District 120 respondents, aspects of the desire to become a customer of PDAM and the ability to pay, especially regarding the desire to be customerPDAM, the overall 53% or 64 respondents who said